2008
DOI: 10.1093/ndt/gfn303
|View full text |Cite
|
Sign up to set email alerts
|

Association of uraemic pruritus with inflammation and hepatitis infection in haemodialysis patients

Abstract: Our study demonstrated the heavy burden of pruritus in HD patients and corroborated the role of inflammation in the pathogenesis of uraemic pruritus. HCV infection is associated with severe uraemic pruritus but is independent of the serum hsCRP level in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 33 publications
3
44
2
1
Order By: Relevance
“…With regards to UP characteristics, our results found that severe pruritus was observed in the studied population, as represented by a median VAS of 7 (5-8), according to the adopted classification in previous studies [9,17,20]. It is important to note that some studies have found an increased mortality risk in patients undergoing dialysis associated with severe pruritus, e.g., when the pruritus VAS score was greater than 7 [17,21].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…With regards to UP characteristics, our results found that severe pruritus was observed in the studied population, as represented by a median VAS of 7 (5-8), according to the adopted classification in previous studies [9,17,20]. It is important to note that some studies have found an increased mortality risk in patients undergoing dialysis associated with severe pruritus, e.g., when the pruritus VAS score was greater than 7 [17,21].…”
Section: Discussionsupporting
confidence: 53%
“…It is important to note that some studies have found an increased mortality risk in patients undergoing dialysis associated with severe pruritus, e.g., when the pruritus VAS score was greater than 7 [17,21]. The DOPPS study found that patients presenting with UP had a 17% greater mortality risk [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary hyperparathyroidism [3,5] and viral hepatitis [19] have been reported to cause pruritus in hemodialysis patients. Thus, we believe clinicians should take particular note of pruritus in hemodialysis patients with secondary hyperparathyroidism or viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Kimmel et al realized that, among the same patients, the ratio of Th1 (measured using CXCR3 as a chemokine receptor and IFN-γ) to Th2 (measured by CCR4 as a chemokine receptor and IL-4) were also higher. In addition, a higher serum level of ferritin and CRP as an acute phase protein and a lower serum level of transferrin and albumin as negative acute phase protein in HD patients with UP compared with the same patients without UP supported the probable role of inflammation in UP (33,34). Additional evidence regarding this immunohypothesis is the decrease in UP following ultraviolet B (UVB) irradiation to even half of the body (35).…”
Section: Discussionmentioning
confidence: 96%